Identification of murine basophils by flow cytometry and histology - Schwartz, Christian; Vöhringer, David (Methods in Molecular Biology, 2014)
Here we describe how murine basophils can be detected in vivo by flow cytometry and immunofluorescence staining. Basophils constitute a homogeneous population of CD4(-)CD19(-)CD49b(+)IgE(+) cells in flow cytometric analysis. When IgE levels are low one can also use anti-Fc?RI or anti-CD200R3 antibodies instead of anti-IgE. For immunofluorescence staining we use an anti-Mcpt8 antibody since Mcpt8 is a specific marker for murine basophils. We describe how to prepare the tissue to cut cryo-sections and how to perform the staining using a tyramide-based amplification kit.
EVALuna2:25874